The Role of Modern Information Technologies in the Study of Historical and Cultural Monuments Ichan Kala - Umida, Tajiyeva; Sirojbek, Allanazarov (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the application of modern digital technologies in the study of historical monuments "Ichan Kala" in Khiva and its practical significance.